THE URGENCY TO INCLUDE GENDER AS PROTECTED GROUP UNDER THE CRIME OF GENOCIDE - Anandy Satrio Purnomo (International Law Department, Faculty of Law Universitas Padjadjaran, 2020)
Abstract This research will discuss exigence to assign gender as protected groups in Genocide under Rome Statute which contains about gender (indeed third gender) selective mass killing. This research is inspired from the allegation of selective mass killing to gender in Nanjing, China, India, and Indonesia which begs protection from crime of genocide. This research method used is the juridical normative approach method. The research is conducted by analyzing the data gained from library studies and international conventions related to International Criminal Law. The specification of research is done by describing the related legislations associated with the legal theory and practice of implementing an object of research. The result of this research shows that the gender has similar characteristics exclusive groups as the protected groups under article 6 Rome Statute. What the result of that based on article 9 Rome Statute, amendment protected group is possible to do. Keywords: Gender, Genocide, International Criminal Court Abstrak Penelitian ini akan membahas urgensi untuk menambahkan gender sebagai kelompok yang dilindungi dalam kejahatan genosida yang diatur di bawah ketentuan Statuta Roma terkait pembantaian berpreferensi gender (termasuk gender ketiga). Penelitian ini terinspirasi dari adanya dugaan pembantaian selektif gender di Nanking, Tiongkok, India, bahkan Indonesia yang membutuhkan perlindungan dari ketentuan genosida. Metode penelitian yang digunakan adalah yuridis normatif. Penelitian dilakukan dengan menganalisis data yang diperoleh dari studi kepustakaan dan studi peraturan konvensi internasional yang berkaitan dengan Hukum Pidana Internasional. Penelitian menggunakan spesifikasi penelitian deskriptif analitis yaitu menggambarkan peraturan yang dikaitkan dengan teori hukum dan praktek pelaksanaan suatu objek penelitian. Hasil dari penelitian menunjukan bahwa gender memiliki karakteristik yang sama dengan kelompok yang dilindungi dalam kejahatan genosida. Sehingga sesuai dengan Pasal 9 Statuta Roma amandemen terhadap kelompok yang dilindungi dalam kejahatan genosida dimungkinkan untuk dilakukan. Kata Kunci: Gender, Genosida, Mahkamah Peradilan Pidana